(untitled) (Applied Biological Research, 2017)
The present study was aimed to compare the genetic diversity among 24 soybean genotypes as revealed by Promoter-anchored amplified polymorphism based on RAPD (PAAP-RAPD) primer-combinations analysis and Inter Simple Sequence Repeat (ISSR) analysis. All the 16 PAAP-RAPD primer-combinations, derived from 4 Promoter-based primers (TA1/G1/CA1/GC1) and 4 RAPD primers (OPE 1/5/7/9) showed amplification, of which 8 were polymorphic. They produced 63 loci, of which 52 were polymorphic. All 20 ISSR primers used were polymorphic generating 115 alleles of which 95 were polymorphic. The similarity coefficient based on ISSR and PAAP-RAPD analysis ranged from 0.67 to 0.93 and 0.41 to 1.00, respectively. The PAAP-RAPD consensus tree revealed 17 clusters; while ISSR revealed all genotypes as separate clusters. In 2D scatter plot, these were broadly classified into 5 major groups. Group-Ia had lowest divergence (MAUS71, KDS 344, KDS387, NRC94, KDS722, Bragg and KDS743) while Group-Ib had low divergence (Birsa Soya1, KDS749, KDS726, KDS739 and JS335). Moderate divergence was observed in Group II (JS9305 and RKS 18) and Group III (Himso 1684, Dsb22 and MACS450). Group IV (KDS741, VLS65, Rpp3 PI462312 variant, EC241778 and PI462312) had highest divergence. Only two genotypes (KDS753 and DS228) were placed separately in both the analyses. The study revealed that PAAP-RAPD has an advantage that it may specifically target regulatory regions of various candidate genes during molecular tagging for a specific trait.